Urinary Liver-Type Fatty Acid-Binding Protein Predicts Progression to Nephropathy in Type 1 Diabetic Patients - Nielsen, Stine Elkjaer (American Diabetes Association, 2010)
OBJECTIVE: Urinary liver-type fatty acid-binding protein (u-LFABP) is a marker of tubulointerstitial inflammation and has been shown to be increased in patients with type 1 diabetes and is further increased in patients who progress to micro- and macroalbuminuria. Our aim was to evaluate u-LFABP as a predictor of progression to micro- and macroalbuminuria in type 1 diabetes. RESEARCH DESIGN AND METHODS: From an inception cohort of 277 patients, u-LFABP, adjusted for urinary creatinine (enzyme-linked immunosorbent assay), was measured in 24-h urine samples from 165 normoalbuminuric patients 9.6 ± 3.5 (mean ±SD) years after onset of type 1 diabetes. The outcome measured was development of persistent micro- or macroalbuminuria or death. RESULTS: Patients were followed for a median of 18 (range 1–19) years; 39 progressed to microalbuminuria, 8 of those progressed further to macroalbuminuria, and 24 died. In a Cox regression model, baseline log u-LFABP levels predicted the development of microalbuminuria, adjusted for known risk factors (sex, age, A1C, systolic and diastolic blood pressure, albumin excretion rate, serum creatinine, and smoking) (hazard ratio [HR] 2.3 [95% CI 1.1–4.6]) and log u-LFABP predicted mortality (adjusted HR 3.0 [1.3–7.0]). u-LFABP (above versus below the median) predicted the development of macroalbuminuria (adjusted HR 2.6 [1.2–5.4]). As a continuous variable, u-LFABP tended to predict macroalbuminuria (HR 1.9, P = 0.2), but numbers were small. CONCLUSIONS: High levels of the tubular inflammation marker u-LFABP predict the initiation and progression to diabetic nephropathy and all-cause mortality, independent of urinary albumin excretion rate and other established risk factors.